Clinical Reasoning of Infectious Diseases Physicians Behind the Use or Nonuse of Transesophageal Echocardiography in Staphylococcus aureus Bacteremia. (28th September 2016) - Young, Heather; Knepper, Bryan C.; Price, Connie S.; Heard, Susan; Jenkins, Timothy C.
Abstract: In this prospective cohort with Staphylococcus aureus bacteremia, transesophageal echocardiography (TEE) was performed in 24% of cases. Consulting Infectious Diseases physicians most frequently cited low suspicion for endocarditis due to rapid clearance of blood cultures and the presence of a secondary focus requiring an extended treatment duration as reasons for foregoing TEE.